2017
DOI: 10.1002/jcph.931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steady‐State Faldaprevir on Pharmacokinetics of Atorvastatin or Rosuvastatin in Healthy Volunteers: A Prospective Open‐Label, Fixed‐Sequence Crossover Study

Abstract: Faldaprevir (FDV) is a potent, orally administered inhibitor of hepatitis C virus protease. It inhibits multiple cytochrome P-450 enzymes and multiple membrane transporters. The objective of this study was to evaluate the effect of steady-state faldaprevir on the pharmacokinetics (PK) of a single dose of atorvastatin or rosuvastatin. In this single-center, open-label, fixed-sequence crossover study, 33 healthy adult male and female volunteers were given either atorvastatin 10 mg (n = 16) or rosuvastatin 10 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
4
4
0
1
Order By: Relevance
“…The study by Hermann et al 42 conducted in healthy subjects treated with multiple doses of 10 mg of ATV for 1 week shows AUC metabolic ratios close to the ones reported in the present study for the active (0.11 for p-OH-ATV, and 0.54 for o-OH-ATV) and inactive metabolites (2.54 for ATV-LAC, 0.42 for p-OH-ATV-LAC, and 1.85 for o-OH-ATV-LAC). Other single oral dose administration studies of ATV reported only the metabolic ratios of AUC for the active metabolite o-OH-ATV, with values of 1.25, 41 1.19, 43 or 0.77 44 and, therefore, close to the value of 1.32 reported in the present study.…”
Section: Lupus Affects Atorvastatin Pharmacokineticssupporting
confidence: 86%
See 1 more Smart Citation
“…The study by Hermann et al 42 conducted in healthy subjects treated with multiple doses of 10 mg of ATV for 1 week shows AUC metabolic ratios close to the ones reported in the present study for the active (0.11 for p-OH-ATV, and 0.54 for o-OH-ATV) and inactive metabolites (2.54 for ATV-LAC, 0.42 for p-OH-ATV-LAC, and 1.85 for o-OH-ATV-LAC). Other single oral dose administration studies of ATV reported only the metabolic ratios of AUC for the active metabolite o-OH-ATV, with values of 1.25, 41 1.19, 43 or 0.77 44 and, therefore, close to the value of 1.32 reported in the present study.…”
Section: Lupus Affects Atorvastatin Pharmacokineticssupporting
confidence: 86%
“…The single oral administration of ATV (20, 40, or 80 mg) to the healthy subjects group (n = 15; Table 3 and Figure 1) resulted in pharmacokinetic parameters of unchanged ATV similar to those reported by Huang et al 41 in the investigation of healthy subjects treated with a single oral dose of 10 mg ATV.…”
Section: Lupus Affects Atorvastatin Pharmacokineticssupporting
confidence: 81%
“…Since aprocitentan was well tolerated, use of a healthy subject population was justified. While the measured plasma concentrations and PK parameters of rosuvastatin alone were similar to published data, [20][21][22] the initial intended LOQ of 1.0 ng/mL was insufficient to reliably characterize the t 1…”
Section: Discussionsupporting
confidence: 66%
“…Since aprocitentan was well tolerated, use of a healthy subject population was justified. While the measured plasma concentrations and PK parameters of rosuvastatin alone were similar to published data, [20][21][22] the initial intended LOQ of 1.0 ng/mL was insufficient to reliably characterize the t 1 2 , and therefore the method was revalidated to lower the LOQ to 0.04 ng/mL. The t 1 2 of rosuvastatin proved to be variable during the study as indicated by a wide 90%CI around the geometric mean.…”
Section: Discussionsupporting
confidence: 66%
“…Rosuvastatin is a substrate of OATP1B1, and interactions have been described with OATP inhibitors. Notably, the interaction with faldaprevir, an OATP‐inhibiting anti‐HCV medication, can lead to increases in AUC and Cmax of rosuvastatin of 15‐ and 33‐fold, respectively …”
mentioning
confidence: 99%